Mutual Fund Clienteles - Fricke, Daniel; Jank, Stephan; Wilke, Hannes (Review of Financial Studies, 2026)
Abstract Using a unique data set on the ownership composition of euro area equity funds, we find substantial differences in the flow-performance sensitivity across mutual fund clienteles. Households, followed by insurers, display the weakest sensitivity, whereas investment funds—as investors in mutual funds—exhibit the strongest sensitivity. Crucially, these behavioral differences hold within the same fund-quarter, ruling out heterogeneity across funds as a potential driver. We relate these clientele effects to monitoring incentives and balance sheet constraints. Lastly, we find that households respond more strongly to poor performance when surrounded by more performance-sensitive investors, indicating strategic interactions in investor flows.